Stop of proton-pump inhibitor treatment in patients with liver cirrhosis (STOPPIT): study protocol for a prospective, multicentre, controlled, randomized, double-blind trial - Wehmeyer, Malte Hermann; Horvatits, Thomas; Buchholz, Anika; Krause, Linda; Walter, Sarah; Zapf, Antonia; Lohse, Ansgar W.; Kluwe, Johannes (Trials, 2022)
Proton-pump inhibitors (PPI) are liberally prescribed in patients with liver cirrhosis. Observational studies link PPI therapy in cirrhotic patients with an increased risk for infectious complications, hepatic encephalopathy and an increased risk for hospitalization and mortality. However, patients with liver cirrhosis are also considered to be at risk for peptic ulcer bleeding. The STOPPIT trial evaluates if discontinuation of a pre-existing PPI treatment delays a composite endpoint of re-hospitalization and/or death in patients (recently) hospitalized with liver cirrhosis compared to patients on continued PPI medication.